The triglyceride glucose-waist-to-height ratio outperforms obesity and other triglyceride-related parameters in detecting prediabetes in normal-weight Qatari adults: A cross-sectional study - Al Akl, Neyla S.; Haoudi, Elias N.; Bensmail, Halima; Arredouani, Abdelilah (Frontiers in Public Health, 2023)
The triglyceride-glucose (TyG)-driven indices, incorporating obesity indices, have been proposed as reliable markers of insulin resistance and related comorbidities such as diabetes. This study evaluated the effectiveness of these indices in detecting prediabetes in normal-weight individuals from a Middle Eastern population. Using the data of 5996 adult Qatari participants from the Qatar Biobank cohort, we employed adjusted logistic regression to assess the ability of various obesity and triglyceride-related indices to detect prediabetes in normal-weight (18.5≤ BMI <25 kg/m2) adults (18 years). Of the normal-weight adults, 13.62% had prediabetes. TyG-waist-to-height ratio (TyG-WHTR) was significantly associated with prediabetes among normal-weight men (OR per 1-SD 2.68; 95% CI (1.67–4.32)) and women (OR per 1-SD 2.82; 95% CI (1.61-4.94)). Compared with other indices, TyG-WHTR had the highest area under the curve (AUC) value for prediabetes in men (AUC: 0.76, 95% CI (0.70–0.81)) and women (AUC: 0.73, 95% CI (0.66–0.80)), and performed significantly higher than other indices (p<0.05) in detecting prediabetes in men. Tyg-WHTR shared similar diagnostic values as FPG. Our findings suggest that the TyG-WHTR index is a better indicator of prediabetes in adult Qatari men of normal weight than other obesity and TyG-related indices